VersaPatch A Low Cost 2.5D Capacitive Touch Sensor - Bittner, Ray; Sinclair, Mike (Proceedings Of HCI 2009, 2009)
Capacitive input devices are becoming increasingly prevalent in consumer devices. This paper presents the hardware and algorithms for the low cost implementation of a capacitive 2.5D input device. The low cost and low power consumption of the device make it suitable for use in portable devices such as cellular phones. The electrical properties used are such that the preexisting snap dome technologies in such devices can be used as capacitive sensing elements, further reducing the cost and size impact of the capacitive sensor.